Experimental comparison of a 2D laminar diffusion flame under oxy-fuel and air atmosphere. (15th January 2018) - Bürkle, Sebastian; Dreizler, Andreas; Ebert, Volker; Wagner, Steven
Abstract: We present an experimental study on the effects of an oxy-fuel atmosphere with 30 %Vol. O2 /70 %Vol. CO2 content on a laminar, non-premixed methane flame based on measured spatial profiles of gas temperature as well as H2 O, CH4, OH and CO concentrations, with the aim of providing thermochemical validation data for numerical simulations in the oxy-fuel context. The in situ measurements were performed using temporally multiplexed laser spectrometer based on direct laser absorption spectroscopy in combination with two-line thermometry. The system is validated on a well-characterized air-blown flame at the same burner and found to be in good agreement with reference data. The different behaviors of the oxy-fuel compared to the conventional air-blown flame with respect to the flame structure, species concentrations and temperature distribution are discussed and explained by the altered thermo-physical properties of the oxy-fuel atmosphere and the reactions involved. The altered stoichiometry of the oxy-fuel flame leads to increased CO and H2 O concentrations, whereas the increased heat transfer and heat capacity caused a reduction in peak flame temperature.